2016
DOI: 10.1515/probus-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity in L2 processing

Abstract: In this paper, we review the current state of the second language (L2) processing literature and report data suggesting that this subfield should now turn its attention to working memory capacity as an important factor modulating the possibility of (near)-native-like L2 processing. We first review three major overarching accounts of L2 processing (Clahsen et al. 2006a Performance similarities between non-native and native speakers. Lingua 120. 901-931) and frame their predictions in terms of the qualitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 73 publications
(103 reference statements)
1
9
1
Order By: Relevance
“…Regarding WM, some recent evidence has shown that WM capacity has a positive relationship with nativelike sensitivity to both L2 agreement violations (Coughlin & Tremblay, 2013) and L2 processing more generally (Linck, Osthus, Koeth, & Bunting, 2014; McDonald, 2006; Miyake & Friedman, 1998; Reichle, Tremblay, & Coughlin, 2016). We might therefore expect similar associations between participants’ WM capacity and the experimental variables as we predicted for proficiency: larger P600 effects, indexing greater sensitivity to L2 agreement violations, and a modulation of the interaction with quantification to resemble the monolingual English speakers’ effect with higher WM capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding WM, some recent evidence has shown that WM capacity has a positive relationship with nativelike sensitivity to both L2 agreement violations (Coughlin & Tremblay, 2013) and L2 processing more generally (Linck, Osthus, Koeth, & Bunting, 2014; McDonald, 2006; Miyake & Friedman, 1998; Reichle, Tremblay, & Coughlin, 2016). We might therefore expect similar associations between participants’ WM capacity and the experimental variables as we predicted for proficiency: larger P600 effects, indexing greater sensitivity to L2 agreement violations, and a modulation of the interaction with quantification to resemble the monolingual English speakers’ effect with higher WM capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have then verified this notion as they found that proficient L2 processors which demonstrate nativelikeness in L2 sentence processing appear to possess high working memory capacity, while the opposite is observed in L2 processors with lower working memory capacity (Coughlin & Tremblay, 2013;Hopp, 2014;Reichle & Birdsong, 2014;Roberts, 2012). Further studies apparently show that the contribution of working memory to L2 sentence processing is not only through its indirect influence on proficiency, but also its own immediate effect on L2 sentence processing (Juffs, 2015;Linck et al, 2014;Reichle et al, 2016). The discussions address the mechanism of holding and refining working interpretation in short-term memory while continuously processing inputted information to achieve a plausible interpretation.…”
Section: Working Memorymentioning
confidence: 88%
“…It is also worthy of notice that there are a few exceptions where other linguistic information may dominate initial syntactic parsing, as in the case of L2 sentence processing (Clahsen & Felser, 2006a, 2006b, and individual differences in proficiency and working memory (Cunnings, 2017;Hopp, 2014;Nakano, Saron, & Swaab, 2010;Reichle, Tremblay, & Coughlin, 2016). These exceptions will be discussed later in their own dedicated section since they might hold some key insights for the L2 sentence comprehension.…”
Section: The Significance Of Syntax In Sentence Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, studies with ERPs and other online measures have provided evidence that L2 learners may show the native-like processing patterns if their L2 proficiency is sufficiently high. The L1–L2 differences may be attributed to their L2 proficiency and cognitive resources ( Just and Carpenter, 1992 ; Hopp, 2006 , 2014 ; Steinhauer, 2006 ; Jackson and Dussias, 2009 ; Steinhauer et al, 2009 ; Roberts, 2012 ; Witzel et al, 2012 ; Reichle et al, 2016 ; Nickels and Steinhauer, 2018 ).…”
Section: Introductionmentioning
confidence: 99%